Letters from and to Joseph Joachim - Joachim, Joseph 1831-1907; Bickley, Nora; Fuller Maitland, John Alexander 1856-1936 (New York Vienna House, 1972)
Often cited as one of the great violinists of all time, Joseph Joachim (1831-1907) also had an "influence on the music of his time that was great beyond possibility of assessment" (J. A. Fuller-Maitland). It is this side of Joachim's life that emerges in these 464 pages of letters to and from: Brahms, Berlioz, Amalie Joachim, Jenny Lind, Franz Liszt, Clara Schumann, Robert Schumann, among many others. In effect a continouus narrative of his life, the letters, beginning in 1844 when he was 13 and ending in 1907, the year of his death, reveal Joachim's extraordinary character, unaffected and direct, and the intensity of his perceptions in matters of the art which was his life.
Originally published in 1914
Selected and translated by Nora Bickley with a preface by J. A. Fuller-Maitland
Keywords: 19th Century (1801-1900); Instrumentalist; Correspondence; Germany; Hungary